Double-edged sword of Workplace Gossip, Performance Pressure and Employee Outcomes, Insights from Affective Events Theory - Rafiq, Sidra; Khan, Naimah; Adnan, Muhammad; Yaseen, Hifza (Journal of Innovative Research in Management Sciences, 2026)
Purpose—The research focuses on the influence of gossip at work, both positive and negative, on the behavioral outcome of employees in the banking industry in Pakistan. The study is based on the Affective Events Theory (AET), which examines the mediating role of performance pressure in the gossip-outcome relationship, as well as the boundary condition of perceived organizational support (POS) in mediating the performance pressure-innovative work behavior (IWB) relationship.Study Design/methodology/approach—A cross-sectional, quantitative research design was used. The survey information was gathered through a structured Likert-scale questionnaire on 320 employees in 4 leading commercial banks in Pakistan: Allied Bank, MCB Bank Limited, Bank al-Habib Limited, and Meezan Bank Limited.Findings—Negative workplace gossip is a strong predictor of both performance pressure and workplace incivility, and performance pressure is a strong mediator in the negative gossip-incivility relationship. Negative gossip has a negative influence on performance pressure.Practical Implications—The findings were challenging for managers in high-pressure service industries, leading them to believe that the problem of gossip management is a psychological or cultural intervention issue. The research shows that positive gossip with the creation of reputational debt is psychologically as uncomfortable as negative gossip, and that performance pressure, irrespective of its social source, is a key cause of workplace incivility.Originality/Value—The current research contributes to the literature of organizational behavior by developing the notion of reputational debt to explain why positive gossip produces obligation-based anxiety in collectivist contexts, offering a more culturally sensitive explanation than the current two-sided sword explanations. It develops a culturally inflected extension of AET by showing that cultural relational logic, namely collectivism and power distance, is not just a contextual.